Mapping genomic hotspots of DNA damage by a single-strand-DNA-compatible and strand-specific ChIP-seq method - Zhou, Zhi-Xiong; Zhang, Mei-Jun; Peng, Xu; Takayama, Yuko; Xu, Xing-Ya; Huang, Ling-Zhi; Du, Li-Lin

(untitled) (Genome Research, 2013)
Spontaneous DNA damage may occur nonrandomly in the genome, especially when genome maintenance mechanisms are undermined. We developed single-strand DNA (ssDNA)–associated protein immunoprecipitation followed by sequencing (SPI-seq) to map genomic hotspots of DNA damage. We demonstrated this method with Rad52, a homologous recombination repair protein, which binds to ssDNA formed at DNA lesions. SPI-seq faithfully detected, in fission yeast, Rad52 enrichment at artificially induced double-strand breaks (DSBs) as well as endogenously programmed DSBs for mating-type switching. Applying Rad52 SPI-seq to fission yeast mutants defective in DNA helicase Pfh1 or histone H3K56 deacetylase Hst4, led to global views of DNA lesion hotspots emerging in these mutants. We also found serendipitously that histone dosage aberration can activate retrotransposon Tf2 and cause the accumulation of a Tf2 cDNA species bound by Rad52. SPI-seq should be widely applicable for mapping sites of DNA damage and uncovering the causes of genome instability.